2015
DOI: 10.1501/vetfak_0000002673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different thawing methods on the quality of meagre fillets

Abstract: Summary:The aim of this study was to determine the effect of different thawing methods (air, refrigerator, water and microwave) on physical, chemical and microbiological quality of meagre fillets which were frozen and stored at -20°C for 21 days. The samples were compared for colour changes, pH, total volatile basic nitrogen (TVB-N), hardness, adhesiveness, total viable count (TVC), total psychrophilic count (TPC) and hydrogen-sulphide producing bacteria (H 2 S). In terms of hardness, refrigerator thawed sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The PV in CVO was higher than values registered in the commercial cod liver oil control oil (CO) for human consumption (2.10 ± 0.53 meq O 2 /kg) (Table 3). None of the CVO we extracted from SBV showed a content lower than 5 meq O 2 /kg, so it was necessary to refine it for the human consumption and, in any case, for further applications [51,52].…”
Section: Yield and Quality Of Crude Viscera Oil (Cvo)mentioning
confidence: 99%
“…The PV in CVO was higher than values registered in the commercial cod liver oil control oil (CO) for human consumption (2.10 ± 0.53 meq O 2 /kg) (Table 3). None of the CVO we extracted from SBV showed a content lower than 5 meq O 2 /kg, so it was necessary to refine it for the human consumption and, in any case, for further applications [51,52].…”
Section: Yield and Quality Of Crude Viscera Oil (Cvo)mentioning
confidence: 99%
“…The thawing process can worsen the texture of frozen fish. Genç et al [26] reported that thawing fish filets decreased the water holding capacity and increased hardness. Low drip loss indicates that HFD can prevent the loss of nutrients and maintain the yield rate during defrosting, even without water use.…”
Section: Drip Loss Of Frozen Raw Mackerelmentioning
confidence: 99%
“…A maximum water temperature of 18 • C was therefore recommended. Genc et al [64] studied quality in terms of color, pH, TVB-N, texture, and bacterial counts of meagre (Argyrosomus regius) fillets subjected to different thawing methods. Filleting took place about six hours post mortem before individual freezing in blast and fluid bed freezers at −20 • C. Fillets were then glazed by immersion in water at 0.2-0.4 • C for 30 sec before frozen storage for 21 days at −20 • C to simulate typical retail conditions.…”
Section: Thawingmentioning
confidence: 99%